Embryonic development of the intestinal villi of the duodenum of the human. - Kovalenko, V. V.; Shesterina, E. K.; Balaco, A. I. (Морфологія / Morphologia / Morfologìâ, 2019)
Background. Knowledge of the stages and mechanisms of embryonic formation of intestinal villi of the duodenum becomes a reliable means to identify the causes and search for ways to prevent such anomalies of its development as atresia and stenosis. Objective: establish features embryonic development intestinal villi of duodenum. Methods. 108 consecutive series of histological sections of embryos and human fetuses from 8 to 70 mm parietal-coccyx length of embryological collection Department of normal anatomy BSMU and 10 series of histological sections of the duodenum human fetuses 21-24 weeks of development are studied. Results. New data on terms and mechanisms of formation and maturing of intestinal villi of duodenum in prenatal development are received. Conclusion. In morphogenesis of intestinal villi of duodenum certain regularity is traced. From 39 days of development, the villi are formed only by protrusion of the epithelium with the underlying mesenchyme, then, Starting from 53 days, also by splitting the already formed villi. From 59 days of embryogenesis, wich is expressed in the occurrence of their definitive forms and lasts until the end of the prenatal development.